Istibdal Wakaf Sebagai Solusi Pendayagunaan Benda Wakaf Masa Post Covid-19: Analisis Pendapat Ulama Mazhab - Tiswarni Tiswarni (Muqaranah, 2023)
This paper explaines the necessity to maintain the sustainability of the benefits of waqf objects, especially waqf for health facilities through istibdal waqf after the Covid-19 pandemic. When the pandemic hit the country, many people were infected by the corona virus outbreak, thus inspiring several Islamic philanthropic institutions to participate in easing the burden on the society and government by raising waqf funds directed at the procurement of medical devices. After Covid-19 hit, even in some regions, there were calls to lift the "pandemic" condition to endemic, then medical devices derived from waqf became no longer used. This makes several institutions, namely Dompet Dhuafa and the Qur'an Waqf Board, think hard about how to utilize the waqf of health facilities so that they continue to benefit the community. The research problem in this paper is how istibdal waqf is a solution to maintain the sustainability of the utilization of waqf objects in the post-COVID-19 period. This type of research is Islamic legal research with qualitative methods. Data were obtained through interviews and documentation and analyzed inductively. The results showed that Dompet Dhuafa and the Qur'an Waqf Board in maintaining the sustainability of the benefits of waqf objects donated several waqf medical devices to several health facilities. Even though giving waqf objects is not allowed by scholars. The solution that DD and BWA can do is to conduct istibdal waqf, so that waqf objects can still be used mauquf 'alaih and are in line with the opinion of the sunny mazhab scholars and positive law in Indonesia.